When time flies: How timelessness determines creative process engagement - Ferreira, A. I. (Creativity Research Journal, 2021)
Based on a model for the experience of timelessness in organisations, this study aims to empirically study the relationship between timelessness and creative process engagement. Research provides an integration of the current model of timelessness by including the dependent variable creative process engagement. With multilevel data, results suggested that timelessness mediated the indirect relationship between individual and work environment variables and creative process engagement. Findings suggested that timelessness was positively related to creative process engagement. Theoretical implications for integrating the construct of timelessness in the creativity literature will be discussed, as well as the practical benefits for managers regarding how to improve timelessness and time management at work.